Immune Checkpoint Blockade in Melanoma – Earlier is Better? - Urbonas, Vincas; Dulskas, Audrius; Baltruškevičienė, Edita; Dabkevičienė, Daiva (Acta medica Lituanica, 2024)
Administering checkpoint inhibition before surgery, known as neoadjuvant therapy, shows promise in treating bulky yet resectable melanomas, and researchers are investigating its potential in various other cancer types. This approach boasts a considerable success in high pathologic response rate, a factor directly linked to survival rates. The routine availability of biopsies presents a distinct chance to comprehend treatment responses. Neoadjuvant ICIs offer advantages like T cell expansion, treatment assessment through surgical specimens, and potential tumor size reduction for better surgical outcomes. However, further research is needed to optimize patient selection and treatment protocols. Erratum note The abstract have been updated to reflect the correct information following a typographical error during typesetting. We apologize for any inconvenience caused by these errors. Below, you will find the corrected version. Corrections were made on 2024-09-01. Updated Abstract Administering checkpoint inhibition before surgery, known as neoadjuvant therapy, shows promise in treating bulky yet resectable melanomas, and researchers are investigating its potential in various other cancer types. This approach boasts a considerable success in high pathologic response rate, a factor directly linked to survival rates. The routine availability of biopsies presents a distinct chance to comprehend treatment responses. Neoadjuvant ICIs offer advantages like T cell expansion, treatment assessment through surgical specimens, and potential tumor size reduction for better surgical outcomes. However, further research is needed to optimize patient selection and treatment protocols.